Self-Criticism and Psychological Well-being: A Study to Find Out the Relationship and Influence on Vocational Students - Mulawarman, M; Afriwilda, M T; Soputan, S D M; Antika, Eni Rindi; Hariyadi, Sigit; Abi F Prabawa; Febrianti, Thrisia (KONSELOR, 2024)
Important for vocational students to achieve psychological well-being amidst technological developments that increase self-critical behaviour. Information overload, increased self-com, and other psychological health issues can increase self-critical behaviour. This can hinder the achievement of the six dimensions of psychological well-being. So, it is necessary to know the correlation between these two variables in vocational students. This study aims to determine the relationship between self-criticism on psychological well-being in vocational students. A total of 1812 students were included, and participants completed assessments of self‐criticism and psychological well-being. The result is self-criticism and psychological well-being is in a medium category with scores M = 60.34; SD = 2.86 and M = 118.48; SD = 2.53 sequentially. Analyses assessed the extent to which the intercept and linear slope of self‐criticism were associated with assessments of psychological well‐being. Findings suggest that a decrease in self-criticism is associated with better psychological well-being in vocational students. There was a relationship between self-criticism and psychological well-being. The implication of this finding suggests applying intervention with a focus on reducing self-criticism to improve student’s psychological well-being.